2008
DOI: 10.1111/j.1751-7893.2007.00055.x
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for using substances in adolescents with and without psychosis

Abstract: Although adolescents with psychosis report using substances for the same reasons as other adolescents, they may also use to self-medicate secondary morbidity associated with psychosis. These results have a number of implications for prevention and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 8 publications
3
19
0
3
Order By: Relevance
“…Interestingly, a study investigating self-reported reasons for cannabis use by UHR individuals yielded enhancement of mood and social motives as primary reasons for cannabis use, whereas motivation for symptom relief was rare (Gill et al, 2015). Using cannabis for mood and social enhancement is consistent with reported reasons for use in first episode psychosis (Pencer and Addington, 2008), and the author’s interpretations were that negative symptoms might drive cannabis use in UHR individuals (Gill et al, 2015). In the current study neuroleptic medication was an exclusion criterion for UHR individuals.…”
Section: Discussionsupporting
confidence: 57%
“…Interestingly, a study investigating self-reported reasons for cannabis use by UHR individuals yielded enhancement of mood and social motives as primary reasons for cannabis use, whereas motivation for symptom relief was rare (Gill et al, 2015). Using cannabis for mood and social enhancement is consistent with reported reasons for use in first episode psychosis (Pencer and Addington, 2008), and the author’s interpretations were that negative symptoms might drive cannabis use in UHR individuals (Gill et al, 2015). In the current study neuroleptic medication was an exclusion criterion for UHR individuals.…”
Section: Discussionsupporting
confidence: 57%
“…The psychometric properties of the CEQ in psychotic populations also requires further exploration. The addition of a non‐psychotic cannabis‐using comparison group would have strengthened the findings, although few differences in reasons for cannabis use between psychotic individuals and other cannabis users have been reported in previous research [40,41]. Recall of cannabis use expectancies may be less reliable among recently admitted psychotic in‐patients, although expectancies are considered to be relatively stable concepts that can be measured over an individual's lifetime [42].…”
Section: Discussionmentioning
confidence: 74%
“…Additionally, patients might have experienced more severe negative effects of smoking cannabis. Relaxation is a consistently reported effect of cannabis in people with and without psychosis (Green et al 2003 ;Pencer & Addington, 2008 ;Dekker et al 2009). Peters et al (in press) found that patients with schizophrenia reported more often than controls to have felt depressed, anxious and suspicious and to have experienced more psychotic symptoms during cannabis intoxication.…”
Section: Discussionmentioning
confidence: 99%